Targeting neuropeptide receptors for cancer imaging and therapy: perspectives with bombesin, neurotensin, and neuropeptide-Y receptors - Morgat, Clément; Mishra, Anil Kumar; Varshney, Raunak; Allard, Michèle; Fernandez, Philippe; Hindié, Elif (The Journal of nuclear medicine (1978), 2014)
Receptors for some regulatory peptides are highly expressed in tumors. Selective radiolabeled peptides can bind with high affinity and specificity to these receptors and exhibit favorable pharmacologic and pharmacokinetic properties, making them suitable agents for imaging or targeted therapy. The success encountered with radiolabeled somatostatin analogs is probably the first of a long list, as multiple peptide receptors are now recognized as potential targets. This review focuses on 3 neuropeptide receptor systems (bombesin, neurotensin, and neuropeptide-Y) that offer high potential in the field of nuclear oncology. The underlying biology of these peptide/receptor systems, their physiologic and pathologic roles, and their differential distribution in normal and tumoral tissues are described with emphasis on breast, prostate, and lung cancers. Radiolabeled analogs that selectively target these receptors are highlighted.